Enhancing Agronomic Practices for Improved Ecosystem Resilience in I and D Operations : A Practice Note - Valieva, Svetlana (World Bank, Washington, DC, 2020)
Water management in irrigated agriculture has been identified as a sustainability challenge due to a combination of continuously increasing demand and the ability of farmers to access water in excess of renewable supply. Intensive irrigation and related agricultural practices can also impair soil and water resources on which they rely by way of pollution and degradation of soil health. Thereby input-intensive farming can generate externalities beyond the intended immediate benefits. These risks are all well understood. However, methods to systematically integrate such measure into irrigation development goals have typically been lacking. Raising the environmental performance of intensive arable production can be accomplished through a broader adoption of good agricultural practice on irrigated land and by enhancing farmers’ skills in soil and water management as well as through related national-level governance strategies. Relevant agronomic practices include those that reducing pollution, improving soil fertility, and enhancing biodiversity can minimize the impacts of agricultural production on natural ecosystems and the services they provide. These also include appropriate matching of crop, soil type, and irrigation methods. Conserving the natural resource base and reducing quality impacts while improving producer net returns is a core objective of WSiA. As a practice of responsible use of natural resources, water stewardship in agriculture (WSiA) responds to sustainability challenges presented by irrigated agriculture by protecting farming operations from resource-related risks as well as minimizing potentially negative impacts on water users and the natural environment.